Electric Field Control of Valence Tautomeric Interconversion in Cobalt Dioxolene - Sanvito, Stefano; Droghetti, Andrea (My University, 2011)
We demonstrate that the critical temperature for valence tautomeric interconversion in cobalt dioxolene complexes can be significantly changed when a static electric field is applied to the molecule. This is achieved by effectively manipulating the redox potential of the metallic acceptor forming the molecule. Importantly, our accurate density functional theory calculations demonstrate that already a field of 0.1??V/nm, achievable in Stark spectroscopy experiments, can produce a change in the critical temperature for the interconversion of 20 K. Our results indicate a new way for switching on and off the magnetism in a magnetic molecule. This offers the unique chance of controlling magnetism at the atomic scale by electrical means.
PUBLISHED
Keywords: Physical chemistry; Cobalt Dioxolene; Nanoscience & Materials